Nano house : innovations for small dwellings - Richardson, Phyllis (Thames & Hudson Inc., 2011)
"Space is at a premium in growing cities. In the countryside, we want to preserve nature and the landscape. And in impoverished parts of the world, the need for sustainable, economical shelter is stronger than ever. At the same time, digital design tools, eco-materials and new prefabrication technologies have led to an explosion in innovative ideas for domestic spaces. Today's challenge for architects and designers is to produce small-scale habitats that are more ecological, flexible and efficient, yet still adhere to modern standards of style and comfort. This book offers the latest and most exciting solutions for anyone seeking to maximize living space with minimal environmental impact."--P. [4] of cover.